An Analysis of Word Formation Processes Found in Instagram - Annisa Faradisa; Zulfadli A. Aziz; Burhanudddin Yasin (Research in English and Education Journal, 2020)
This thesis was conducted to focus on the word formation processes found in Instagram. Words also underwent some processes in their formation. The research method of this study was descriptive qualitative. This study used documentation as  its instruments. The theoretical framework of word-formation processes was promoted by Delahunty and Garvey (2010) and Plag (2003). The data were obtained through document analysis. The writer found that there were 38 words of acronym, 17 words of borrowing, 15 words of abbreviation, five words of blending, two words of coinage, and one word of affixation from the total of 78 data found. It can make the conclusion that the aim of different types of word formation processes assisted people to understand the function of each word formation processes in order to avoid mistake in their writing. Expectantly, it might be useful for other researchers who are interested in word formation processes.